LITERARY VOCABULARIES IN INDONESIAN - I Dewa Putu Wijana (Aksara, 2024)
This article deals with Indonesian literary vocabularies with the attention focus on their categories, morphological forms, semantic fields, language origin, and functions. By exploiting reflective and introspective, and empirical method, the data are collected intuitively  through various genres of song lyric lines. They are further classified in accordance with those four problems. Through careful observation and analysis toward the data collection, the research can reveal that the Indonesian literary vocabularies include various categories. There are vocabularies which have very different and similar forms from their ordinary equivalents yielded from varieties of phonological and morphological processes. The literary vocabularies are taken from various sources, such as Malay, Sanskrit, Old Javanese, and Arabic. They can be simply classified into content and functional words that cover a wide range of semantic fields. In spite of their main use for beautifying the linguistic expressions, their existence can also be exploited for intensifying them, and to keep equal to (scientific) foreign terms.